Bibliometric analysis of worldwide scientific production in taekwondo (Revista de Artes Marciales Asiáticas, 2025)
Taekwondo has experienced rapid growth over the last three decades, solidifying its position as one of the most prominent combat sports worldwide. The objective of this study was to analyze the academic output on taekwondo published in scientific journals using bibliometric methods. The search included publications up to December 31, 2024. Data was collected in the Scopus and Web of Science databases using Bibliometrix and VOSviewer software. The results showed that the oldest publication date back to 1979, with a notable upward trend in publications starting in 2010. A total of 1982 publications were found, of which 26 have 100 or more citations. Up to 689 scientific journals, 4979 authors and co-authors were associated with the publications. A total of 2480 academic institutions from 80 countries were identified, with South Korea, China, and Brazil being the countries with the highest number of publications. Additionally, South Korea and Brazil had the largest number of international collaboration networks. Despite the growing scientific production, the field presents structural weaknesses, such as an uneven distribution of author productivity and limited long-term engagement in taekwondo research from most researchers. Furthermore, some research domains within taekwondo, particularly those related to physical performance, appear to be developing faster than others, such as sociocultural or pedagogical perspectives.